Delirious New York by Rem Koolhaas (diségno, 2021)
On January 23, 1931, a brief notice was published in the New York Times in which it was reported that the annual Beaux Arts Ball would be held in the evening at the Hotel Astoria [AAVV 1931a]. This is the twelfth time that this event is repeated –the first was dedicated to the theme of Venice through the centuries, held in 1912– and it promises to be full of surprises. The ball will be masked, with a specific request to wear costumes “of the modern era” and in which “fantasy should be the note for subscribers to follow” [AAVV 1931a, p. 29]. [read more]